DEVELOPMENT OF RURAL TOURISM IN THE MUNICIPALITY OF GORNJI MILANOVAC-AN EXAMPLE FOR VILLAGES IN SERBIA - Miladin M. Ševarlić; Zlatana Petrović (Ekonomika Poljoprivrede (1979), 2011)
Rural tourism in Serbia is increasingly becoming one of the most important and profitable additional activities, while in the successful rural households it is their main economic activity. Beside the mountain town and resort Rudnik, several villages (Koštunići, Trudelj, Brusnica, Klatičevo, Leušići, Gojna Gora, ...) have acquired an image of distinctive tourist destinations. Their results confirm the leading position in the municipality of Gornji Milanovac in Moravički districts as well as respectability in the rural tourism supply of Serbia. This paper presents the basic indicators of the rural tourism development in the municipality of Gornji Milanovac (number of registered households, categorized rooms, beds and guests; realized revenue), with special emphasis on the 2002-2009 period. Based on the researching results for the municipality of Gornji Milanovac, there is given an estimate of the potential impact of rural tourism in the Republic of Serbia.